Allocation Of Green Open Space In The Church Courtyard As Green Ecclesiology Implementation - Manuahe, Mick R.; Poluan, Agnes Relly; Rampengan, Priscila F. (International Journal of Education, Information Technology, and Others, 2025)
This study highlights the urgency of implementing Green Open Space (RTH) in church environments as a form of green ecclesiology. The environmental crisis due to climate change and exploitation of natural resources demands the active involvement of various sectors, including the church, in maintaining ecological balance. The church plays a strategic role in shaping the ecological awareness of the congregation and becoming an agent of change in environmental conservation. This study uses a qualitative descriptive method with a literature review approach to explore the ecological, social, and spiritual benefits of RTH, as well as the challenges faced in its implementation. The results of the study show that the presence of RTH in churches contributes to improving air quality, reducing environmental temperatures, and providing space for spiritual reflection and social interaction of the congregation. However, in its implementation, the church faces obstacles such as limited land, lack of congregation awareness, and lack of regulatory and financial support.